FUTURE OF X-RAY SCANNERS IMPLEMENTATION IN UKRAINIAN AIRPORTS - Ivannikova, V. Y.; Gavryluk, A. A.; Nadutenko, T. V. (Science-based technologies, 2013)
Increasing efficiency of aviation transport functioning in Ukraine is impossible without optimization of the technology of airport formalities, namely aviation security check. Analysis of aviation security technologies, used in international Ukrainian airports, shows that in our country security check with only basic full-body scanners are mainly used for these purposes. However, globalization processes, implementation of new technologies worldwide require adjustment of Ukrainian aviation transport infrastructure to the international standards in aviation safety in order to provide high competitive ability of our state on the world market. Main advantages and disadvantages of X-rays scanners have been investigated and presented in the article. It is determined that one of the most important aspects of X-ray scanners usage is their influence on people’s health. Investigations have shown that exposure to radiation and to electric and magnetic fields associated with passenger screening devices is not expected to cause adverse health effects on passengers. Radiation levels used by the technologies under consideration in this article are far below the levels that have been linked to health effects. Generalized methodology of technological parameters calculation of passengers handling in an airport during passing aviation security check with usage of the X-ray scanners is presented in the article. The methodology is based on the appropriate determination of inbound flow intensity of passengers during peak loading at the airport; passengers flow intensity that comes through the registration; passenger handling intensity. Example of aviation security check area calculation according to the formed methodology, taking into account installed by investigations passengers handling intensity, productivity of X-ray scanners and expenses on their operation, is presented in the paper. Investigation of the problem shows necessity of new X-ray scanners installation in the international Ukrainian airports. The research also gives to aviation enterprises and state authority clear understanding of the potential of aviation security check newest technologies as an innovative form of climatic financing.